QOLP-13. PSYCHOSOCIAL DISTRESS IN PATIENTS WITH RECURRENT MENINGIOMAS. (5th November 2018) - Randazzo, Dina; Kirkpatrick, John; McSherry, Frances; Herndon, James; Affronti, Mary; Johnson, Margaret; Vaslow, Zachary; Lipp, Eric; Desjardins, Annick; Friedman, Henry; Peters, Katherine
Abstract: INTRODUCTION: Meningiomas, the most common CNS neoplasm, are often deemed less threatening than their glial counterparts. Unfortunately, these tumors recur and necessitate surgery, radiation, and/or systemic treatment. We explored the psychosocial distress of patients with recurrent meningioma using The National Comprehensive Cancer Network Distress Thermometer (NCCN-DT) and Problem List. METHODS: This was a retrospective analysis of patients with recurrent meningioma seen at the Preston Robert Tisch Brain Tumor Center between 12/31/2004–10/10/2018 who completed a NCCN-DT and Problem List. The first or only NCCN-DT assessment after initial recurrence was used for analysis with a score of 4 indicating moderate to severe distress. RESULTS: 45 patients were identified, 56% female, median age was 61 years and 58% had unifocal disease. 60% were Grade 1, 33% Grade II, 4% Grade III, and 2% indeterminate recurrent meningioma. The median NCCN-DT score was 3, and 49% had a NCCN-DT score 4 indicating moderate to severe distress. 64% of females vs 30% of males reported distress scores 4 (p=0.04). 65% of patients with unifocal disease reported 4 scores compared to 26% with multifocal disease (p=0.02). Fatigue (N=24), Worry (N=23), Nervousness (N=22), Depression (N=19) and Memory/Concentration (N=19) were the most commonly reported problems. A higher incidence of worry among females (64%) than males (35%) was the only problem showing a trend towards significance (p=0.08). Between initial recurrence and NCCN assessment, the type and number of treatments patients received included: surgery (median=1, range 0–5), radiation (median=2, range 0–5), systemic treatment (median=2, range 0–12). There was no association between distress and the number of surgeries (p=0.99), radiation treatments (p=0.49) or systemic therapies (p=0.87). CONCLUSIONS: In our study population, nearly half of recurrent meningioma patients reported moderate to severe distress. Therefore, even in this benign tumor population, the NCCN-DT and problem list should be administered at every clinic visit.